PERAN WORLD HEALTH ORGANIZATION (WHO) DALAM MENANGGULANGI WABAH VIRUS ZIKA DI BRASIL - Yonathan Sahala Wibowo; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to explain “the role of the World Health Organization(WHO) in tackling the outbreak of the zika virus in Brasil.The Zika virus originally appeared in 1947 and was found    in a rhesus monkey in the Zika Forest.Viral zika in brasil began to spread to parts of latin America from Asia.This Virus spread when there was a race to paddle canoes in 2014 ago in the south pacific areaThe research data obtained from books, journals, official documents, theses, and websites. The author uses the pluralism approach and the analysis of the roles of the international organization. The method of the research is qualitative which is the data obtained from the literature related to the research topic.                 The result of the research shows there is a significant role of the World Health Organization in tackling the outbreak of zika virus in reality first, WHO conducts Supervision by tracking and detecting zika infected areas quickly. So that it can be known quickly the extent of the spread of the zika virus. then, Advancing research in the prevention, control and control of Zika virus infections and related complications. WHO conducts supervision by tracking and detecting areas infected with the zika virus quickly. So that it can be known quickly the extent of the spread of the zika virus. Keyword:Zika Virus,Brasil,WHO,Role